Designing a Lecture Room Monitor System with an Android Application Based on the Chip's ESP8266 - Ari Yuliati; Fajar Hafid Abdilah; Eddy Samsoleh (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2020)
The classroom monitoring system with an android application based on the ESP8266 chip was created to solve problems on campus in finding unused rooms and to provide solutions to the problems of finding classroom thus far by using inefficient manual methods. The monitor system was made to determine the status of classroom usage with a passive infrared (PIR) sensor which functions to detect human presence in the room and a light sensor with a Light Dependent Resistor (LDR) to detect the use of the projector in the room. The two sensors are connected to the ESP8266 chip which is connected to a realtime database via the internet. The android application is specifically made to access monitoring data stored in a realtime database throughout it is connected to the internet. The results of this system test the PIR sensor reaches a maximum distance of 4 meters, a time delay of about 3 minutes, a reliable tool, and low cost.